Inhibitory effects of alternaramide on inflammatory mediator expression through TLR4-MyD88-mediated inhibition of NF-кB and MAPK pathway signaling in lipopolysaccharide-stimulated RAW264.7 and BV2 cells. (25th January 2016) - Ko, Wonmin; Sohn, Jae Hak; Jang, Jae-Hyuk; Ahn, Jong Seog; Kang, Dae Gill; Lee, Ho Sub; Kim, Jong-Su; Kim, Youn-Chul; Oh, Hyuncheol
Abstract: Alternaramide (1 ), a novel lipophilic depsipeptide, has been isolated from the extract of the marine-derived fungus Alternaria sp. SF-5016. In the course of extensive biological evaluation of1, its anti-inflammatory effects in lipopolysaccharide (LPS)-stimulated RAW264.7 and BV2 cells were observed. In our initial study of the anti-inflammatory effects of1, the compound suppressed production of nitric oxide (NO) and prostaglandin E2 (PGE2 ) in LPS-stimulated RAW264.7 and BV2 cells. Suppression of NO and PGE2 production was correlated with the inhibitory effect of1 on expression of LPS-induced inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) at the protein level in RAW264.7 and BV2 cells. In addition, 1 reduced production of pro-inflammatory cytokines, including tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), IL-6, and IL-12 in LPS-stimulated RAW264.7 and BV2 cells. In the evaluation of the molecular mechanisms underlying the anti-inflammatory effects of1, the compound was found to suppress the nuclear factor-kappa B (NF-κB) signaling pathway in RAW264.7 and BV2 cells stimulated with LPS. This suppression was mediated by disruption of phosphorylation and degradation of IκBα, an inhibitor of NF-κB, in the cytoplasm, and blocking of nuclear translocation of the NF-κB p50–p65 heterodimer. Furthermore, 1 inhibited phosphorylation of c-Jun N-terminal kinases (JNKs) and p38 mitogen-activated protein kinase (MAPK), demonstrating its capacity to inhibit MAPK signaling. Finally, 1 markedly reduced expression of Toll-like receptor 4 (TLR4) and myeloid differentiation primary response gene 88 (MyD88) at the mRNA and protein levels in LPS-stimulated RAW264.7 and BV2 cells. Taken together, the results of the present study suggest that1 modulates several TLR4-mediated inflammatory pathways, demonstrating its potential in the treatment of inflammatory and neuroinflammatory conditions. Highlights: Alternaramide showed anti-inflammatory effects in LPS-stimulated cells. Alternaramide suppressed activation of NF-кB pathway. Alternaramide suppressed activation of JNK and p38 pathway. Alternaramide suppressed TLR4 and MyD88-mediated pathways in LPS-stimulated cells.